Psychopedagogical intervention: an experience in a private educational center - Calderón Calderón, Roxana (2003)
The Worldwide recent events, as a globalization product have incidence on education. In last decades this situation has caused that the role of the School Psychologist in private institution has got greater importance and responsibility, increasing psycho pedagogic intervention levels. The author presents her labor experience